Does America Need a Foreign Policy? : Toward a Diplomacy for the 21st Century - Kissinger, Henry 1923- (New York Simon & Schuster, 2001)
The former Secretary of State under Richard Nixon argues that a coherent foreign policy is essential and lays out his own plan for getting the nation's international affairs in order.
Include Notes and Index
Keywords: United States -- Diplomatic relations -- International relations